2017
DOI: 10.1038/s41598-017-08118-3
|View full text |Cite
|
Sign up to set email alerts
|

The N-P-K soil nutrient balance of Portuguese cropland in the 1950s: The transition from organic to chemical fertilization

Abstract: Agricultural nutrient balances have been receiving increasing attention in both historical and nutrient management research. The main objectives of this study were to further develop balance methodologies and to carry out a comprehensive assessment of the functioning and nutrient cycling of 1950s agroecosystems in Portugal. Additionally, the main implications for the history of agriculture in Portugal were discussed from the standpoint of soil fertility. We used a mass balance approach that comprises virtually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 58 publications
0
32
0
6
Order By: Relevance
“…Fertilization plays an important role in promoting the initial growth and improving the quality of rootstock 10,11 , for example, Silva 12 found that superphosphate promoted the height and stem diameter of plants to the greatest extent after 30 d of transplanting. Ciriello 13 reported that a there was a trend of increase in plant height and leaf area with addition of nitrogen (N), while the stem diameter and root dry mass data showed a negatively linear way.…”
mentioning
confidence: 99%
“…Fertilization plays an important role in promoting the initial growth and improving the quality of rootstock 10,11 , for example, Silva 12 found that superphosphate promoted the height and stem diameter of plants to the greatest extent after 30 d of transplanting. Ciriello 13 reported that a there was a trend of increase in plant height and leaf area with addition of nitrogen (N), while the stem diameter and root dry mass data showed a negatively linear way.…”
mentioning
confidence: 99%
“…Considering the soil N budget at the Po River watershed level, the agricultural areas with the highest N surpluses correspond to the studied watersheds [86]. Such excesses of N are among the highest reported in Europe and North America [87][88][89][90][91][92]. The average areal surplus peaked in the Oglio watershed portion (193 kg N ha −1 year −1 ), and was similar for Adda and Mincio (139 and 136 kg N ha −1 year −1 , respectively).…”
Section: Excess Manure Availability and Use Of Synthetic Fertilizers mentioning
confidence: 80%
“…O excedente, ainda, pode provocar externalidades negativas como aumento da salinidade do solo e a eutrofização (VITOUSEK et al, 2009). Dessa forma, o correto manejo nutricional do solo deve buscar um saldo próximo ao equilíbrio entre entrada e saída de nutrientes (CUNHA et al, 2014;CARMO et al, 2017).…”
Section: Introductionunclassified
“…(2016) ao estudarem o solo Chinês. Carmo et al (2017) estudaram os impactos do uso de fertilizantes inorgânicos no solo português. Na Espanha, os efeitos da mudança socioecológica, ocorrida no meio rural sobre o nível de nutrientes no solo, foram analisados por Molina et al (2015).…”
Section: Introductionunclassified